Biblioteca virtual temática em saúde focada nas necessidades do usuário e na usabilidade - Fonseca, Leandro Guedes da (2012)
This work discusses usability features that can be applied on interfaces for virtual libraries, to meet differences in interaction and information needs of different users. It presents the emergence and popularization of the Internet and presents it as a determining factor for the development of thematic virtual libraries. It presents the history of libraries and proposes subsidies for the creation of thematic virtual libraries issues aimed to meet the needs of users. It introduces the concept of information and health information. It discusses the interdisciplinary relations of Information Science with Cognitive Science. It demonstrates, through a focus group study on information needs of potential users of a thematic virtual library. It talks about usability in virtual libraries and usability features as parameters for meeting the needs of users. We conclude that the heuristic evaluation and usability principles raised in the literature and the current technical standards on the subject present subsidies for improvement of thematic virtual libraries and we consider the views gathered in focus groups are important contributions to the improvement of processes in a thematic virtual library in health.